Estimating Healthcare Expenditures for Northern Europe and the Baltic Region: Revisiting the Baumol Model - Singh, Shailender; Singh, Amar; Mohan, Arvind; Gour, Tanuja (Ekonomika, 2024)
The study aims to empirically test Baumol’s cost disease hypothesis about to the secular rise in healthcare expenditures for Northern Europe and the Baltic region in recent decades. Panel data regressions and adjusted Baumol variables are applied to the data for 11 countries of Northern Europe and the Baltic region from 2000 to 2019. The results highlight that Baumol’s cost disease partly drives the secular rise in healthcare expenditures in the countries studied. The Baumol cost disease is estimated to be around 0.01 to 0.05 for current health expenditure, 0.07–5.48 for public health expenditure, and 3.14–6.23 for private health expenditure. This finding suggests that achieving a balanced growth in different sectors of the economy may result in separating the health sector from having a Baumol’s effect in the countries studied.